IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING METHOD FOR BEST PERFORMING EMPLOYEE SELECTION (CASE STUDY AT NATIONAL STANDARDIZATION AGENCY OF INDONESIA) - Yuwan Jumaryadi (IJISCS (International Journal of Information System and Computer Science), 2020)
Technological developments can help human in their work. National Standardization Agency of Indonesia often gives awards for each employee based on the achievements of an employee. With the award given, it is expected that employees will motivated to provide the best work results for the company. The current rating system for National Standardization Agency of Indonesia employees is still by distributing questionnaires, then the results of the questionnaire are recapitulated and ranked based on the highest score to the lowest value. The assessment process currently take a long time so the information obtained is not fast. With the existing problems, we need a system that can help the company in determining the best employees with predetermined criteria. Based on the problems that occur, it need decision support system that can help the company to choose the best employee. The method used in decision making is Simple Additive Weighting (SAW). Decision making with Simple Additive Weighting method is used for decision making using the weighted addition method. Calculations in employee evaluations are carried out directly by superiors with prescribed considerations. The system developed can determine the employees who have the best performance, and helpful for decision maker to make final decision.